Relationship between Peer Influence and Consumption of Sugar-Sweetened Beverages in Adolescents - Pamarta, Dina; Suminah, -; Sumardiyono, - (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Consumption of Sugar-Sweetened Beverages (SSBs) in Indonesia among adolescents is high at 72%. Nevertheless, identical adolescent behaviour is to be accepted by the peer group.Peer groups have a high probability of influencing the consumption of adolescents. Objective: To determine the relationship between peer influence and consumption of SSBs in adolescents. Methods: The study employed an observational design with a cross-sectional approach. The sample consisted of 115 senior high schoolsstudents in the Surakarta area. Peer data collection and consumption of SSBs were conducted by filling out online questionnaires independently by adolescents. After data collection, analysis was done using Chi-square test. Results: Our data showed that there is a relationship between peer influence and consumption of SSBs with value (p=0.000). Conclusion: Peer influence is an important factor in consumption of SSBs in adolescents. International Journal of Human and Health Sciences Vol. 06 No. 03 July’22 Page: 289-291